Peranan Hukum Rahasia Dagang Dalam Pembangunan Ekonomi: Undang-Undang Dan Putusan - Akbar, Tantowi (UI Scholars Hub, 2022)
There are five qualities required for a law to be said to have a role in the economic development of a country: stability, certainty, justice, education, and the special abilities of lawyers. One of the laws in Indonesia which closely related to the national economy is Trade Secret Law Number 30 Year 2000. This trade secret law should be able to comply these qualities. Therefore, this trade secret law has a role in national economic development in Indonesia. On the other hand, the Verdic of the Supreme Court of the Republic of Indonesia Number 332K/Pid.Sus/2013 concerning trade secret matter could provide legal education to the wider community.